Germinação de sementes de stryphnodendron mart. osmocondicionadas - Kissmann, Camila [UNESP]; de Silvana, Paula Quintão Scalon; Mota, Leandro Henrique de Sousa; Vieira, Maria do Carmo (My University, 2010)
The objective of this study was to evaluate the germination of seeds of three species of Stryphnodendron Mart. (Stryphnodendron adstringens (Mart.) Coville, S. obovatum Benth. and S. polyphyllum Mart.) under priming in different osmotic agents, in osmotic potentials of -1.0 MPa and -0.5 MPa. Seeds scarified in concentrated sulphuric acid for 40 minutes were conditioned in the following treatments: 1) PEG 6000; 2) PEG 6000 + KNO3, in equal parts; 3) KNO3; 4) Water and 5) Control. Afterwards, they were incubated in a germination chamber (BOD type) at a temperature of 20 °C (± 2 °C) during 0 h (control), 6 h, 12 h and 24 hours, under continuous light. For each species, the experiment was carried out in a completely randomized factorial with 5 (priming treatments) x 4 (priming time) factors and four repetitions of 20 seeds. The percentage of germination, germination speed index, length of root and aerial parts, and fresh and dry mass of seedlings obtained from seeds conditioned in -1.0 MPa osmotic potential and the %G and IGS of those conditioned at -0.5 MPa, were evaluated. Priming in the potential of -1.0 MPa did not significantly influence the physiological performance of Stryphnodendron obovatum and S. polyphyllum seeds but the development of S.adstringens seeds was adversely affected. Priming of S.adstringens and S.polyphyllum seeds in potential of -0.5MPa results in higher percentage germination and germination speed index.
Germination of primed seeds of stryphnodendron mart
Keywords: Germination; Polyethylene glycol 6000; Preconditioning; Savanna; Stryphnodendron